Effect of Water and Salt on the Colloidal Stability of Latex Particles in Ionic Liquid Solutions - Dóra Takács; Matija Tomšič; Istvan Szilagyi (Colloids and Interfaces, 2021)
The colloidal stability of sulfate (SL) and polyimidazolium-modified sulfate (SL-IP-2) latex particles was studied in an ionic liquid (IL) of ethylammonium nitrate (EAN) and its water mixtures. Aggregation rates were found to vary systematically as a function of the IL-to-water ratio. Repulsive electrostatic interactions between particles dominated at low IL concentrations, while they were significantly screened at intermediate IL concentrations, leading to destabilization of the dispersions. When the IL concentration was further increased, the aggregation of latex particles slowed down due to the increased viscosity and finally, a striking stabilization was observed in the IL-rich regime close to the pure IL solvent. The latter stabilization is due to the formation of IL layers at the interface between particles and IL, which induce repulsive oscillatory forces. The presence of the added salt in the system affected differently the structure of the interfaces around SL and SL-IP-2 particles. The sign of the charge and the composition of the particle surfaces were found to be the most important parameters affecting the colloidal stability. The nature of the counterions also plays an important role in the interfacial properties due to their influence on the structure of the IL surface layers. No evidence was observed for the presence of long-range electrostatic interactions between the particles in pure ILs. The results indicate that the presence of even low concentrations of water and salt in the system (as undesirable impurities) can strongly alter the interfacial structure and thus, the aggregation mechanism in particle IL dispersions.